مدى تطبيق مناهج الصفّ الرابع الأساسي لمدخليّ (حلّ المشكلات و البيئي) من مداخل التعليم التكاملي (دراســـة ميدانية في محافظة اللاّذقية) - الياس, أسما; حمراء, روز (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يهدف البحث إلى تعرّف مدى تطبيق مناهج الصفّ الرابع الأساسي وفق مدخليّ حلّ المشكلات والبيئي من مداخل التعليم التكاملي, واعتمد البحث المنهج الوصفي، وتكوّنت العيّنة من (357) تلميذاً وتلميذة و(113) معلّماً ومعلّمة, و(23) موجهاً وموجهة, واستخدم لجمع البيانات استخدمت: استبانة للموجهين وأخرى للمعلمين والتلاميذ, وبطاقة ملاحظة لأداء المعلّمين. وخلُص البحث إلى عدّة نتائج أهمّها: درجة متوسطة لتطبيق كلٍّ من مدخل حلّ المشكلات والمدخل البيئي في عملية تعليم مناهج الصفّ الرابع الأساسي, وتفاوتاً ملحوظاً بين إجابات التلاميذ والمعلمين والموجهين على الاستبانة الخاصّة بكلٍّ منهم؛ التفاوت الكبير بين مدارس التعليم الأساسي في مدى توافر الوسائل والتقنيات التعليمية المُساعدة في تطبيق مناهج الصفّ الرابع الأساسي وفق مداخل التعليم التكاملي؛ وجود فروق ذات دلالة إحصائية بين متوسطات آراء المعلّمين ونتائج بطاقة الملاحظة المُطبّقة عليهم في مدى التطبيق الفعلي لمدخلي (حل المشكلات والبيئي)؛ كما خلُص إلى مُقترحات أهمّها: تخصيص الوقت الكافي للمجالات العملية, بما يسمح للتلاميذ بالتدريب على المجالات التي يختارونها, وتوفير وسائل تكشف عن الميول والقدرات الخاصّة لدى التلاميذ للعمل على تنميتها, وأن يُراعى في تصميم المباني المدرسيّة استجابتها لمُتطلبات التعليم التكاملي كالحاجة للمعامل والمخابر والملاعب. The research aims to identify the extent of the application of the fourth grade primary curriculum in accordance the solving problems and environmental entrances from integrative education entrances, and adopted the search descriptive approach, and the sample consisted of (357) pupils and (113) teachers, and (23) directed, to collecting data :the researcher used ,Questionnaires for teachers, pupils and directed, and note card for the performance of teachers. The research found several results including: medium degree to apply the problems solving and environment entrances, in the process of teaching fourth grade primary curriculum, and remarkable disparity between the responses of students, teachers and mentors to their respective resolution; the great disparity between the basic education schools in the availability of tools and techniques of educational assistance in the application of the fourth grade primary curricula according to the entrances of integrative education; difference statistically significant between the averages of the views of teachers and the results of observation applied them card in the extent of the actual application of the entrances differences (problem-solving and environmental); also concluded proposals including: the allocation of time to the areas of operation, allowing students training in their chosen fields, and provide the means reveal tendencies and special abilities of students to work on development, and to take into account in the design of school buildings to respond to the requirements of integrative education such as the need for laboratories and playgrounds